2011
DOI: 10.1063/1.3659287
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transmission in rolled-up hyperlenses utilizing Fabry-Pérot resonances

Abstract: We experimentally demonstrate that the transmission though rolled-up metal/semiconductor hyperlenses can be enhanced at desired frequencies utilizing Fabry-Pérot resonances. By means of finite difference time domain simulations we prove that hyperlensing occurs at frequencies of high transmission.Metamaterials offer the possibility to tailor their effective optical parameters 1,2 allowing e.g. sub-wavelength imaging. Beside metamaterials with negative index of refraction 3-5 , metamaterials consisting of alter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Although the intrinsic metal loss is unavoidable, the hyperlens can be optimized by increasing the amount of the dielectric component or working at longer wavelengths. A higher optical transmission can also be realized with resonant structures 40,41 . Moreover, instead of conformal film deposition, fabrication based on rolled-up technology provides an alternative method for controlling film conformality and roughness [41][42][43][44] .…”
Section: Experimental Hyperlens Demonstration and Recent Advancesmentioning
confidence: 99%
“…Although the intrinsic metal loss is unavoidable, the hyperlens can be optimized by increasing the amount of the dielectric component or working at longer wavelengths. A higher optical transmission can also be realized with resonant structures 40,41 . Moreover, instead of conformal film deposition, fabrication based on rolled-up technology provides an alternative method for controlling film conformality and roughness [41][42][43][44] .…”
Section: Experimental Hyperlens Demonstration and Recent Advancesmentioning
confidence: 99%
“…Advanced concepts in inorganic semiconductor nanomembrane (NM) science and technology lead foundations for emerging classes of three-dimensional tubular nano/ micro-architectonics. [1][2][3] These tubular architectures, realized by a rolled-up technique, are of interest due to their widely innovative applications in energy storage, 4 robotics, 5,6 electronics/phonics, [7][8][9][10][11][12] and optoelectronics. 13 With elaborate designs of geometry or surface chemistry during the rolling up process, the corresponding physical properties and device performances can be artificially tuned.…”
mentioning
confidence: 99%
“…On the other hand, several studies to enhance the transmission through the lenses have been reported. Higher optical transmission was realized with the Fabry-Perot resonance mechanisms 25 26 27 and the radius-dependent permeability for an impedance-matched condition 28 . In the acoustic counterpart, the zero-mass effect has been implemented 29 30 31 to overcome the thickness limitation rising from resonance based lens 32 33 which restricts the device’s thickness to be chosen depending on the operating frequency.…”
mentioning
confidence: 99%